Sales Information System Utilizing 13.56 MHz RFID Member Cards for Enhanced Efficiency in Cooperative Stores - Dani Yusuf; Denis Ahmad (LPPM Universitas Islam 45 Bekasi, 2024)
This research aims to produce an output in the form of a cooperative sales application to its members using a 13.56 MHz RFID membership card. The research was conducted at Toko Koperasi Ubhara Jakarta Raya, which is a cooperative owned by employees of Universitas Bhayangkara Jakarta Raya, from January 2024 to February 2024. The cooperative membership card, which contains a 15.56 MHz RFID chip, can be used to validate cooperative member data when shopping at the cooperative store. With this application, it is hoped that it can simplify sales transactions for members and minimize input errors by store personnel. The system development method in this research uses the prototype method, the application is developed using native PHP programming language, and the database used is MySQL. The application created is expected to assist the cooperative in selling its products using a 13.56 MHz RFID card for better data management and quick presentation of sales reports.